Aldous Huxley's ideological development, 1919-1936 - Bradshaw, JD (1987)
Based on numerous magazine and newspaper materials which are not documented in the standard bibliography of his canon and an abundance of unpublished letters, this thesis provides a conspectus of Aldous Huxley's socio-political activities between 1919 and 1936 and offers an interpretation of his ideological development during the period. The bedrock of Huxley's thought was his dread of Americanization and his concomitant advocacy of intellectual aristocracy. The contribution various figures made to the formation of Huxley's opinions, such as Vilfredo Pareto and D.H. Lawrence, is assessed in full. Chief among these influences were H.L. Mencken and H.G. Wells. Mencken's role in Huxley's ideological development is at present unacknowledged, while Huxley is currently perceived as Wells's ideological adversary, not his peer. A discussion of Huxley's responses to the crisis of 1929-1932 forms the cornerstone of the thesis. His sorties into the alien England's of mechanized labour and the unemployed, his exasperation at parliamentary inertia, his brief connection with Political and Economic Planning and his rejection of its gradualism in favour of a more draconian, Soviet-style approach, lastly, his interest in eugenics and the creation of a rigid order of castes, are seen as the logical developments from his quasi-fascist position in the 1920s. The "nightmarish" World State of AF 632 is revealed as a simulacrum of the authoritarian blueprint he championed as an urgent national expedience at the time he was writing Brave New World. Further evidence of Huxley's belief in planning is provided in an appraisal of Now More Than Ever, a play of his which, hitherto, has been presumed lost. Finally, Huxley's incongruous emergence as a cynosure of the anti-fascist intelligentsia and his subsequent withdrawal into Greggism is surveyed in detail.